2017 IEEE International Symposium on Information Theory (ISIT) 2017
DOI: 10.1109/isit.2017.8006567
|View full text |Cite
|
Sign up to set email alerts
|

Denoising linear models with permuted data

Abstract: The multivariate linear regression model with shuffled data and additive Gaussian noise arises in various correspondence estimation and matching problems. Focusing on the denoising aspect of this problem, we provide a characterization the minimax error rate that is sharp up to logarithmic factors. We also analyze the performance of two versions of a computationally efficient estimator, and establish their consistency for a large range of input parameters. Finally, we provide an exact algorithm for the noiseles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Specifically, we assume that Y i relates to X = [X 1 , ..., X n ] T only through (Π i· XW) T , where X i and Y i lie on the surface of a p-dimensional unit sphere denoted by S p−1 , W ∈ R p×p is an orthogonal translation matrix satisfying WW T = I p with I p an identity matrix, and Π = [Π T 1· , ..., Π T n· ] T ∈ R n×n is a mapping matrix that corrects the potential mismatch. There is a growing literature on the shuffled linear regression problem of Y i = (Π i· XW) T + U i when Π is a permutation matrix encoding only one-to-one correspondence between X and Y and no orthogonality constraint is imposed on W (Pananjady et al 2017a,b, Slawski & Ben-David 2017, Abid et al 2017, Hsu et al 2017, Unnikrishnan et al 2018. It has been shown that the least squares estimator of W is generally inconsistent without any additional constraints imposed on Π (Pananjady et al 2017a,b, Slawski & Ben-David 2017.…”
Section: Spherical Regression With Mismatched Datamentioning
confidence: 99%
“…Specifically, we assume that Y i relates to X = [X 1 , ..., X n ] T only through (Π i· XW) T , where X i and Y i lie on the surface of a p-dimensional unit sphere denoted by S p−1 , W ∈ R p×p is an orthogonal translation matrix satisfying WW T = I p with I p an identity matrix, and Π = [Π T 1· , ..., Π T n· ] T ∈ R n×n is a mapping matrix that corrects the potential mismatch. There is a growing literature on the shuffled linear regression problem of Y i = (Π i· XW) T + U i when Π is a permutation matrix encoding only one-to-one correspondence between X and Y and no orthogonality constraint is imposed on W (Pananjady et al 2017a,b, Slawski & Ben-David 2017, Abid et al 2017, Hsu et al 2017, Unnikrishnan et al 2018. It has been shown that the least squares estimator of W is generally inconsistent without any additional constraints imposed on Π (Pananjady et al 2017a,b, Slawski & Ben-David 2017.…”
Section: Spherical Regression With Mismatched Datamentioning
confidence: 99%
“…If we assume perfect particle picking, then the cryo-EM model (II.2) is a special case of (VI.1) when G is the group of 3-D rotations SO(3) and T is the linear operator that takes the rotated structure, integrates along the z-axis (tomographic projection), convolves with the PSF, and samples it on a Cartesian grid. The MRA model formulates many additional applications, including structure from motion in computer vision [5], localization and mapping in robotics [69], study of specimen populations [51], optical and acoustical trapping [32], and denoising of permuted data [61].…”
Section: A Multi-reference Alignmentmentioning
confidence: 99%
“…Nevertheless, it has only been until very recently that the problem of shuffled linear regression has been considered in its full generality. In fact, the main achievements so far have been concentrating on a theoretical understanding of the conditions that allow unique recovery of ξ * or Π * ; see [8], [28], [9], [10], [29], [11], [31], [32], [33], [18], [34], [35], [36], [19]. Letting A be drawn at random from any continuous probability distribution, [10] proved that any such ξ * can be uniquely recovered with probability 1 as long as 2 m ≥ 2n.…”
Section: Prior Artmentioning
confidence: 99%